Association between C reactive protein and depression in a population of healthy adults: the Cooper Center Longitudinal Study. (21st March 2020) - Khan, Amber; Leonard, David; Defina, Laura; Barlow, Carolyn E; Willis, Benjamin; Brown, E Sherwood
Abstract : The relationship between depression and inflammation is currently a topic of much interest. Previous studies have produced mixed results regarding the association between depression and high-sensitivity C reactive protein (hs-CRP). The aim of this report was to determine the association between hs-CRP and depression in a large sample of healthy adults. This is a cross-sectional study of 26, 638 healthy adults seen for preventive medical examinations between December 2000 and August 2018 at the Cooper Clinic in Dallas, Texas. Multivariable logistic regression was used to evaluate the association between hs-CRP levels and depressive symptoms as measured by the 10-item Center for Epidemiologic Studies Depression Scale. Covariates included race, age, education, smoking history, alcohol use, menopausal status, body mass index (BMI), and medication use. The Hs-CRP level demonstrated a weakly positive association with depressive symptoms (OR 1.06 per mg/L, 95% CI 1.03 to 1.09 for women; OR 1.05 per mg/L, 95% CI 1.02 to 1.09 for men) that became insignificant when controlling for BMI in women (OR 1.02 per mg/L, 95% CI 0.98 to 1.05) and men (OR 1.02 per mg/L, 95% CI 0.98 to 1.05). Adjusting for antidepressant and statin use did not affect the association between hs-CRP and depressive symptoms in women (OR 0.99 per mg/L, 95% CI 0.96 to 1.03) or men (OR 1.01 per mg/L, 95% CI 0.97 to 1.05). Levels of hs-CRP were not associated with depression independent of BMI in a predominantly white, male population of higher socioeconomic status. This finding suggests that associations between hs-CRP and depression may be explained by obesity, which warrants further investigation into shared pathways between obesity and depression.